Visionary Film : the American Avant-Garde, 1943-2000. - Sitney, P. Adams (Oxford University Press, 2002)
Critics hailed previous editions of Visionary Film as the most complete work written on the exciting, often puzzling, and always controversial genre of American avant-garde film. This book has remained the standard text on American avant-garde film since the publication of its first edition in 1974. Now P. Adams Sitney has once again revised and updated this classic work, restoring a chapter on the films of Gregory J. Markopoulos and bringing his discussion of the principal genres and major filmmakers up to the year 2000.